A Study on Occupancy and Compressive Strength of Concrete with Produced Injection Method. (28th May 2014) - Ekinci, Cevdet Emin; Kelesoglu, Omer
Abstract : Concrete is a composite construction material made primarily of aggregate, cement, and water. Fresh concrete must have certain features. These are shown in durability, workability, compressive strength, flexural strength, shrinkage, impact resistance, wear, and so forth. In this study, compressive strength, erosion, and attrition behavior of concrete with silica fume additive produced by injection method were researched. Concrete with high occupancy is produced with injection. Use of more than 10% silica fume increases the fresh concrete's need for mixed water significantly. It was observed that as the ratio of silica fume additive increases, concrete becomes stronger against compression, erosion, and attrition.